Redesign a model of 32 inch LCD TV bracket - Zaitun, Mohd Desah (2009)
This project is about redesign and fabricating a model of 32 inch LCD TV bracket. It is function to mount the 32 inch LCD TV to the wall in vertical position more efficiently. This project involves the process of redesigning a model for 32 inch LCD TV bracket by considering the shape and also the ergonomic factor for people to use. After the design has completed, it was transformed to its model product where the design is used for guideline. This project also required analysis to make sure the strength of the product to ensure the safety for the user indeed of publishing. Numerous methods and process involve in this project for assembly each parts by using bolt, lag bolt, lag washer, bolt washer and washer. This project is mainly about redesign a model for 32 inch LCD TV by referring to an existing product as guidience. This new product is design for 32 inch screen LCD TV that is mount to the wall vertically in static. The weight is more light, the panel thickness also thicker than the existing product and the price is more cheaper and affordable. After all the process had been done, this model of 32 inch LCD TV bracket may help us to understand the fabrication and redesigning process that involved in this project.